Fuzzy Stability of Euler-Lagrange Type Cubic Functional Equation: A Fixed Point Approach (Journal of Informatics and Mathematical Sciences, 2012)
In this paper, the authors investigate the generalized Hyers-Ulam stability of Euler-Lagrange type Cubic functional equation \begin{align} 2af(x+ay)+2f(ax-y) =(a^3+a)[f(x+y)+f(x-y)]+2(a^4-1)f(y)\end{align} in fuzzy normed space by direct method and fixed point method, where $a$ is fixed integer with $a eq 0$, $± 1$.
Keywords: Fuzzy normed space; Cubic functional equation; Generalized Hyers-Ulam stability